Comparative Efficacy of Xianling Gubao Capsules in Improving Bone Mineral Density in Postmenopausal Osteoporosis: A Network Meta-Analysis - Luo, Ming-hui; Zhao, Jin-long; Xu, Nan-jun; Xiao, Xiao; Feng, Wen-xuan; Li, Zi-ping; Zeng, Ling-feng (Frontiers in Endocrinology, 2022)
Objective The clinical efficacy of Xianling Gubao capsule (XLGB) and its combination therapy in the treatment of postmenopausal osteoporosis (PMOP) was systematically evaluated by frequency-based network meta-analysis. Methods We searched the China National Knowledge Infrastructure (CNKI), Wanfang, SinoMed, PubMed, Embase and Cochrane Library databases to identify clinical trials of XLGB for the treatment of PMOP from the establishment of each database to November 22, 2021. The quality of the included studies was evaluated by using the risk of bias assessment tool version 2.0 (Rob 2.0) recommended by Cochrane. Stata 14.0 was applied for statistical analysis of the data, and the surface under the cumulative ranking curve (SUCRA) was used to rank the intervention measures of each outcome index. Results This study included 22 clinical trials (including 19 RCTs and 3 non-RCTs) involving 12 drug therapies. According to the results of the network meta-analysis and SUCRA, the best three interventions for improving lumbar bone mineral density (BMD) are XLGB+BP+calcium (83.7%), XLGB+BP (68.5.7%) and XLGB+VD (67.1%). XLGB+calcium was the best combination regimen for improving femoral neck BMD and increasing bone Gla protein (BGP) and alkaline phosphatase (ALP) contents in serum. The SUCRA values of XLGB+calcium for improving the three outcome indicators were 68.0%, 59.5% and 82.1%, respectively. Conclusions The results of this network meta-analysis show that combined application of XLGB can effectively improve BMD and serum BGP and ALP compared to calcium alone, VD or BP. In the future, multicentre, large-sample and double-blind clinical RCTs should be carried out to supplement and verify the results of this study.